Self-Leadership Transformation: Enhancing The Development and Performance of Human Capital Management Professionals - Rismawati Br Sitepu; Henry Susanto Pranoto; Wahyudi Henky Soeparto; Teofilus Teofilus; Sanju Kumar Singh (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: Self-leadership is increasingly recognized as an important competency for enhancing performance and professional development, among mid- to senior-level professionals in Human Capital Management (HCM). As the work environment is rapidly evolving, mid- to senior-level HCM professionals must transform the way they manage themselves and their teams and enhance their ability to innovate and be role models. Objectives: This study explores the factors that foster self-leadership in mid- to senior-level professionals in Human Capital Management. Design/Methodology/Approach: Using a qualitative approach, we conducted in-depth interviews with 15 mid- to senior-level HCM professionals from various companies. Thematic analysis was applied using the Gioia Corley methodology to identify self-leadership factors such as self-reflection self - goal setting, self-monitoring, continuous learning, and self-reward. Findings/Results: The results show that the implementation of self-leadership contributes substantially to the improvement of skills, motivation, overcoming complex organizational challenges, and employee engagement, in the HCM development program. The transformation that occurs includes changes in the way of manages oneself and leads, which is part of the professional development process. Conclusion: The implementation of self-leadership strategies has been proven to accelerate professional development, and encourage employees to be more proactive, adaptive, and independent, to changes in the work environment. Originality/Value (State of the art): This study shows the importance of self-leadership training and implementation to improve performance, encourage individual initiative, and build a positive work culture. Keywords: self-leadership, human capital management, professional performance transformation, qualitative research, development program